2020
DOI: 10.1186/s13613-020-00696-2
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of nasogastric tube insertion by SORT maneuver (sniffing position, NGT orientation, contralateral rotation, and twisting movement) versus neck flexion lateral pressure in critically ill patients admitted to ICU: a prospective randomized clinical trial

Abstract: Background: Although many techniques have been introduced to facilitate nasogastric tube (NGT) insertion using anatomic landmarks and a group of devices, there is a lack of general consensus regarding a standard method. The current study purposed to investigate if SORT maneuver (sniffing position, NGT orientation, contralateral rotation, and twisting movement) increases the success rate of NGT correct placement versus neck flexion lateral pressure (NFLP) method. Methods: A randomized controlled trial study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…For this, methods without the aid of instruments are described, i.e. : head flexion 28 , lateral neck pressure 29 , tube freezing 20 , measurement with corrected formula of the tip of the ear-lobe to the xiphoid process , reverse Sellick´s maneuver 20 , compression on the cricoid cartilage [28][29] , sort maneuver 19 and gastric insufflation 41 .…”
Section: Discussionmentioning
confidence: 99%
“…For this, methods without the aid of instruments are described, i.e. : head flexion 28 , lateral neck pressure 29 , tube freezing 20 , measurement with corrected formula of the tip of the ear-lobe to the xiphoid process , reverse Sellick´s maneuver 20 , compression on the cricoid cartilage [28][29] , sort maneuver 19 and gastric insufflation 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Broadly, the methods can be classified as "device based" and "manipulation of posture" or maneuvers. 5 Many modifications of blind technique, such as "neck flexion" 1 "neck flexion with lateral pressure" technique, 6 reverse Sellick's manoeuvre, 7 and frozen NGT technique 8 have been used to facilitate NGT insertion with variable success. In the recent past, there is a brief mention that insertion of NGT after placement of throat pack is possible.…”
Section: Nasogastric Tube Insertion In Anesthetized Intubated Adult P...mentioning
confidence: 99%
“…Feasibility of NGT insertion and the number of attempts for intubation matter as well, when it comes to a safe bedside practice. The first clinical trial reporting successful employment of SORT maneuver for NGT insertion in unconscious patients admitted to intensive care unit was just recently published with promising results [ 6 ]. This study showed that ease of insertion was considerably greater and success rate was much higher for SORT maneuver than the other conventional technique of neck flexion and lateral pressure.…”
mentioning
confidence: 99%